Anti-Obesity Property of Lichen Thamnolia vermicularis Extract in 3T3-L1 Cells and Diet-Induced Obese Mice - Choi, Ra-Yeong (Prev Nutr Food Sci, 2017)
Thamnolia vermicularis (TV) is an edible lichen that is prevalent in the alpine zone of East Asia. This study evaluated the feasibility of using TV acetone extracts as a functional food based on experiments using cell line and obese mice. The cellular triglyceride levels and Oil red O staining of 3T3-L1 cells indicated that TV extracts (5 and 10 μg/mL) dose-dependently suppressed adipocyte differentiation and lipid accumulation compared with the control. The TV extract (0.4%, w/w) in a high-fat diet (HFD) was supplemented to C57BL/6N mice for 12 weeks, and TV extract supplement significantly reduced visceral fat mass and body weight compared with HFD feeding alone. The TV extract also induced significant decreases in serum and hepatic lipids, whereas it increased the serum high-density lipoproteins-cholesterol/total cholesterol ratio and fecal lipids levels. Moreover, the TV extract led to significantly lower homeostasis model assessment of insulin resistance in diet-induced obese mice. Taken together, these results suggest that the TV extract may have anti-obesity effects, including lipid-lowering, and it is a natural resource with the potential for use in obesity management.